Positive and negative effects in creatine supplementation in sports - Pavlovic, R.; Vrcic, M. (7. medunarodni simpozijum "SPORT I ZDRAVLJE", Tuzla 10. - 11. 10. 2014, 2014)
Creatine is used in muscle cells to store energy for running and exercise of explosive type. Athletes can increase the amount of creatine in the muscles by taking creatine supplements. Some research suggests the positive effects of creatine use while other studies deny it. According to some authors dosed use of creatine enhances performances of sprint up to 5% and with repeated accelerations up to 15%. As for the long-term effects, the use of creatine for a month or two during the training enable the progress in sprint running up to 8%, in strength to 15% and increase of body mass by 3%. The only known side effect is weight gain.